Konstruksi Etika Tabayyun Digital Dalam Al-Quran Sebagai Paradigma Literasi Media Pendidikan Agama Islam - Mumu Zainal Mutaqin; Sunarto Sunarto (Fakultas Agama Islam UNDARIS, 2026)
AbstractThe purpose of this study is to analyze and describe in depth the construction of digital tabayyun ethics based on Q.S. Al-Isra’ verse 36 within the framework of the Islamic Religious Education learning media literacy paradigm in society. Specifically, this study aims to identify tabayyun values that are relevant to the digital context, examine how the integration of these values occurs in the PAI learning process, and evaluate the role of teachers and the educational environment in shaping critical, selective, and responsible media behavior.This study uses a qualitative approach with a literature study type; this approach was chosen because the focus of the study lies in conceptual and normative analysis of written sources, including the Qur’an, hadith, books, and scientific articles relevant to the theme of digital tabayyun and media literacy in PAI. The data collection technique in this study was carried out through documentation, namely by collecting various secondary data sources such as tafsir books, reference books, scientific journals, as well as curriculum documents relevant to digital-based Islamic Education learning.The concept of tabayyun ethics in QS Al-Isro verse 36 provides a theological basis that all information must be based on clear and accountable knowledge, thereby shaping critical and ethical awareness in receiving and spreading information in the digital space. In the context of media literacy, the value of tabayyun is then constructed into a competency framework that includes the ability to critically analyze, evaluate, and verify religious content, while also instilling an attitude of caution, honesty, and digital responsibility. In its implementation as a paradigm of PAI learning, digital tabayyun ethics are systematically integrated into learning outcomes, learning processes based on analysis and fact-checking, as well as the formation of students' digital character reflected in behavior that does not easily spread information and is able to communicate politely in digital media.